Efficacy of the use of perfluorocarbon as a temporary tamponade agent in severe ocular trauma and/or complex retinopexy: a scoping review (2024)
Background Perfluorocarbon (PFC)possesses unique chemical properties that favor the pigment epithelium’s adhesion and allows the drainage of subretinal fluid through retinal holes present in retinal detachment cases. However, PFC as a temporary tamponade agent has been limited due to its high potential for toxicity. Main body We conducted a scoping review regarding the use of PFC in vitreoretinal surgery as a temporary tamponade in subjects with severe ocular trauma or severe retinal detachment who received a therapeutic intervention (vitrectomy via posterior approach with the use of PFC as a temporary tamponade), compared to vitrectomy without the use of PFC as a temporary tamponade. Outcomes of interest were retinal reattachment, visual acuity (VA), postoperative complications and retinal toxicity. The search was performed in Medline, Medline In-Process & Other Non-Indexed Citations, Medline Daily Update, Embase databases. Reference lists from relevant review articles were also included. Two hundred thirty-eight studies were found, with no duplicate entries. In the first selection, 230 articles were eliminated; in the second selection, 6 additional articles were discarded. In total, 8 articles were obtained in this review. Two selected articles corresponded to animal studies and 6 to studies in humans. Regarding study design, 5 were case series, and 1 was a cohort study. Conclusion PFC as a short-term tamponade had high rates of reapplication, improved VA, and the most frequent adverse effects were reversible after PFC withdrawal. Nonetheless, the quality of the studies was poor. Studies with more rigorous methodologies are needed to determine visual and structural outcomes and potential risks of PFC use as a temporary tamponade in vitreoretinal surgery.